2018
DOI: 10.1159/000490046
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Anxiety and Depression before and after Alcohol Detoxification: Anxiety and Depression as Gender-Related Predictors of Relapse

Abstract: Background/Aims: The aim of this prospective study was to estimate gender differences in anxiety, depression, and alcohol use severity among patients with alcohol use disorder (AUD) before and after detoxification program and within 12 months after discharge. Methods: AUD severity, state and trait anxiety, and depression were assessed in 187 patients entering an inpatient alcohol detoxification program. Follow-up assessments were performed at 6 and 12 months after discharge. A between- and within-subjects anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…A third study also found that women were more likely to report high anxiety and depression at alcohol detoxification admission and discharge compared to men. 29 In that study, both genders showed increased anxiety and depression symptoms at 6-month follow-up, with more anxiety symptoms predicting men’s relapse at 12-month follow-up and more depression symptoms predicting women’s relapse at 12-month follow-up. 29 …”
Section: Biopsychosocial Sex and Gender Differences In Alcohol Use Anmentioning
confidence: 80%
“…A third study also found that women were more likely to report high anxiety and depression at alcohol detoxification admission and discharge compared to men. 29 In that study, both genders showed increased anxiety and depression symptoms at 6-month follow-up, with more anxiety symptoms predicting men’s relapse at 12-month follow-up and more depression symptoms predicting women’s relapse at 12-month follow-up. 29 …”
Section: Biopsychosocial Sex and Gender Differences In Alcohol Use Anmentioning
confidence: 80%
“…As the child ages, psychiatric disorders may manifest. Adolescents (age 13‐18) with FASD have a high prevalence of suicidal ideation (35.2%) and suicide attempts in males [19.5 times higher than normal,136]. Depression and anxiety disorders are common, postulated to be due to life‐long dysregulation of the hypothalamic‐pituitary‐adrenal (HPA) axis [137] and continue until adulthood [138].…”
Section: Fetal Alcohol Spectrum Disorder (Fasd)mentioning
confidence: 99%
“…Women were also more likely than men to think that improvement in alcohol‐use would occur without help (47% versus 24%) and thus less likely to seek therapy [16]. Unfortunately, women, due to lower body mass and free body water, are more prone to alcohol related complications than men, including cirrhosis [17], cardiovascular disorders [18], mental health disorders [19] and death [20].…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a common psychiatric disorder that can occur at different age groups [ 6 ]. Although there are multiple medications used for managing depression, treatment success is usually low, especially in patients with alcohol dependence or SUDs [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…The association between substance use and depression has been specified more significantly for some substances, including alcohol, cannabis, and opioids. Some data are also available on stimulant agents and benzodiazepines [ 6 ].…”
Section: Introductionmentioning
confidence: 99%